THE ROLE OF ARTIFICIAL INTELLIGENCE IN THE FORMATION OF THE INNOVATIVE EDUCATIONAL ENVIRONMENT IN THE USA - Alisher Serikbayev (American Journals, 2025)
The article analyzes the impact of artificial intelligence (AI) technologies on the formation of an innovative educational environment in the United States. The study examined modern adaptive learning platforms, virtual assistants, and educational analytics methods that are actively used in university and online educational programs. Based on the analysis of empirical data, key benefits of implementing AI technologies were identified and recommendations for further development of educational practices were formulated. The results obtained confirm the strategic importance of AI for transforming education and creating flexible, student-centered learning systems.
Keywords: Artificial intelligence, innovative educational environment, virtual assistants, personalized learning, USA, online education.